2021
DOI: 10.1021/acs.biomac.0c01802
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Human Lysozyme Amyloid Fibrillation by ACE Inhibitor Captopril: A Combined Spectroscopy, Microscopy, Cytotoxicity, and Docking Study

Abstract: Misfolding proteins could form oligomers or amyloid fibers, which can cause a variety of amyloid-associated diseases. Thus, the inhibition of protein misfolding and fibrillation is a promising way to prevent and treat these diseases. Captopril (CAP) is an angiotensin-converting enzyme inhibitor (ACEI) that is widely used to treat diseases such as hypertension and heart failure. In this study, we found that CAP inhibits human lysozyme (HL) fibrillation through the combination techniques of biophysics and bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…The extent of protein aggregation after a prolonged incubation period can be understood from Congo red binding assay. The binding of CR to the β-sheet structures of protein fibrils leads to an increased absorption intensity along with a red-shift in peak position when compared with that observed in native protein Figure S6 shows the spectral changes of CR absorption in HEWL protein solutions prepared at different time periods (0 h, 40 h, 60 h) of incubation in the absence and presence of bile acids.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of protein aggregation after a prolonged incubation period can be understood from Congo red binding assay. The binding of CR to the β-sheet structures of protein fibrils leads to an increased absorption intensity along with a red-shift in peak position when compared with that observed in native protein Figure S6 shows the spectral changes of CR absorption in HEWL protein solutions prepared at different time periods (0 h, 40 h, 60 h) of incubation in the absence and presence of bile acids.…”
Section: Resultsmentioning
confidence: 99%
“…Human lysozyme (HL) was selected as a protein model to explore the inhibitory effects of catechol-o-methyltransferase inhibitor (Entacapone) and angiotensin-converting enzyme (ACE) inhibitor (Captopril) on amyloid aggregation. 35,36 AFM images showed that the number and length of fibrils decreased significantly when HL was co-incubated (1 : 10) with these drugs. Researchers synthesized a series of tacrine-benzothiazoles heterodimers derivatives through structure-based rational drug design.…”
Section: Topographical Imaging Of Protein-drug Interactionmentioning
confidence: 99%
“…To date, only two strategies are being used to treat AD patients: acetylcholinesterase inhibitors to maintain the level of acetylcholine in the brain and N -methyl- d -aspartate receptor antagonists to prevent excitotoxicity, but none of them alter the progression of disease . Over several years, other strategies have been studied to reduce or disrupt the Aβ assemblies, including immunotherapeutic vaccines, antibodies, peptides, , natural compounds, and repurposing drugs. Because of the AD drug development failures, new strategies like repurposing of drugs have emerged as a viable strategy with the potential to interfere with the underlying disease mechanisms of AD and slow its progression . Due to rising problem of antibiotic resistance, repurposing of antibiotics for treating other disease seems to be a plausible option.…”
Section: Introductionmentioning
confidence: 99%